PARAMETRIC COST ESTIMATION USING ACTIVITY BASED COSTING FOR PRISMATIC PRODUCT MACHINING - Indah Widiastuti; Subagyo Subagyo; Janu Pardadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2012)
The study is focuses on a parametric cost model to estimate cost at the early stages of prismatic product development by machining process. The initial phase of model development begins with the determination of cost based on Activity-based costing (ABC) method of trough the overhead cost allocation of some product variants. All the resources required in the machining process are grouped into cost centers similar rates in order to determine the cost center (cost center rate). The Resources are derived from financial statements based on costs incurred during the period of time. Cost activity is calculated based on the amount of consumption and tariff cost centers required of each activity. Main activity the machining process, which develop a cost model with its parameters is the cost driver activity (activity cost driver) concerning on the amount of production and batch sizes. Mathematical equation based feature dimension has been created to determine machining process time as one of the parameters of the model, create a. Feature were classified into 4 (four) groups of slots / pockets, holes, drills and chamfer. They are used as input variables to calculate the machining time. Thus, input parameters into the cost equation are the available information at the design stage, namely: the number of tools, product weight, dimensions (size) and the type of product features.